The Effect of Congklak Games on Numeracy and Islamic Values in Early Childhood - Yuniarti; Musi, Muhammad Akil; Sugiarti , Tri (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study examines the effect of the traditional congklak game on the development of numeracy skills and Islamic values in early childhood education. The study addresses a gap in the literature, as many previous studies tend to separate cognitive development from spiritual and moral formation, despite the holistic orientation of Islamic pedagogy. While congklak has been widely recognized for its contribution to early mathematical skills, its potential role in fostering Islamic values such as honesty, patience, and cooperation has received limited scholarly attention. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The participants consisted of 28 children aged 5–6 years selected through purposive sampling at TK Al-Alaq Barombong. Data were collected through structured observation, numeracy tests, and documentation, and were analyzed using the Mann–Whitney U test. The results show a statistically significant difference between the experimental and control groups (Z = −4.513; p = 0.001), with an average increase of 18.93 points in numeracy scores among children who participated in congklak-based learning activities. These findings indicate that congklak is not only effective in improving numeracy skills but also serves as a meaningful medium for internalizing Islamic values through interactive and rule-based play. Therefore, this study recommends the integration of traditional value-based games into early childhood curricula to support holistic development encompassing intellectual, social, and spiritual dimensions.